Megathyrsus maximus addition in total mixed ration on performance, metabolism, and quality of lamb carcasses - Sant'Anna, Milton Augusto Cassiano [UNESP]; Carlis, Matheus Sousa Paula de; Polizel, Daniel Montanher; Ferreira, Evandro Maia; Andrighetto, Cristiana [UNESP]; Luz, Patricia Aparecida da [UNESP]; Araujo, Leandro Coelho de [UNESP] (Univ Federal Santa Maria, 2025)
This study assessed the impact of total mixed ration silage of Megathyrsus maximus harvested with 70 cm composed of Megathyrsus maximus harvested at 70 cm in height and concentrate at the time of silage or total mixed ration of grass cut at 70 cm composed of Megathyrsus maximus harvested with 70 cm in height (in Exp. I and III) and total mixed ration silage cut at 130 cm composed of Megathyrsus maximus harvested 130 cm height and concentrate at the time of silage or total mixed ration of Megathyrsus maximus harvested with 130 cm composed of Megathyrsus maximus harvested at 130 cm height (in Exp. II and IV), on rumen metabolism, nutrient digestibility, and the performance and carcass characteristics of feedlot lambs. The results showed that TMRS70 increased ruminal pH in Exp. I and TMRS130 exhibited higher ether extract digestibility, propionic concentration, and lower acetic to propionic ratio and ruminal pH compared to TMR130 in Exp. II. In Exp. III and IV, there was no significant effect on the performance and quality of the carcass. However, in Exp. IV, TMRS130 led to decreased dry matter intake and average daily gain, while lambs fed with TMR130 showed a higher rib-eye area. Total ration ensilage could be used as a conservation method for young grasses (70 cm) without impairing performance, metabolism, carcasses, and meat quality. However, further research is recommended to evaluate the economic analysis of feeding total ration ensilage (70 cm) instead of total mixed ration as a forage conservation method.
Keywords: Palavras-chave; efici & ecirc;ncia alimentar; cordeiros; pastagens tropicais; nutri & ccedil;& atilde;o animal